Prox1 Is a Marker for AII Amacrine Cells in the Mouse Retina - Luis Pérez de Sevilla Müller; Shaghauyegh S. Azar; Janira de los Santos; Nicholas C. Brecha; Nicholas C. Brecha; Nicholas C. Brecha; Nicholas C. Brecha (Frontiers in Neuroanatomy, 2017)
The transcription factor Prox1 is expressed in multiple cells in the retina during eye development. This study has focused on neuronal Prox1 expression in the inner nuclear layer (INL) of the adult mouse retina. Prox1 immunostaining was evaluated in vertical retinal sections and whole mount preparations using a specific antibody directed to the C-terminus of Prox1. Strong immunostaining was observed in numerous amacrine cell bodies and in all horizontal cell bodies in the proximal and distal INL, respectively. Some bipolar cells were also weakly immunostained. Prox1-immunoreactive amacrine cells expressed glycine, and they formed 35 ± 3% of all glycinergic amacrine cells. Intracellular Neurobiotin injections into AII amacrine cells showed that all gap junction-coupled AII amacrine cells express Prox1, and no other Prox1-immunostained amacrine cells were in the immediate area surrounding the injected AII amacrine cell. Prox1-immunoreactive amacrine cell bodies were distributed across the retina, with their highest density (3887 ± 160 cells/mm2) in the central retina, 0.5 mm from the optic nerve head, and their lowest density (3133 ± 350 cells/mm2) in the mid-peripheral retina, 2 mm from the optic nerve head. Prox1-immunoreactive amacrine cell bodies comprised ~9.8% of the total amacrine cell population, and they formed a non-random mosaic with a regularity index (RI) of 3.4, similar to AII amacrine cells in the retinas of other mammals. Together, these findings indicate that AII amacrine cells are the predominant and likely only amacrine cell type strongly expressing Prox1 in the adult mouse retina, and establish Prox1 as a marker of AII amacrine cells.